Modifikasi Proses Pembuatan Dodol - Haryadi Haryadi; Sai'in Sai'in; Suhardi Suhardi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1998)
Preparation of a traditional starch-based sweet (dodol) involved mixing or blending of ingredients comprising glutinous rice flour, coconut milk, coconut sugar, and water with continous stirring until a semi-elastic mass is obtained. The process is labourious and lengthy. Effort were made to simplify and shorten the process by modification of the steps of preparation. Modification I involves steaming of the mixture of glutinous rice flour and water, pounding the cake, boiling the pounded cake with sugar solition; Modification H steaming of the mixture of glutinous rice flour and water, pounding the cake, steaming the mixture of pounded cake and sugar solution; Modification III soaking glutinous rice, boiling the rice with coconut milk, pounding the cake, boiling the punded cake with sugar solution; Modification IV soaking glutinous rice, boiling the rice with coconut milk, pounding the cake, and then steaming the mixture of pounded cake and sugar solution. The resultant dodols were analyzed for water and reducing sugar, the sensoriy of dodol was characterized, and the length of processing steps was evaluated. The result indicated that processes involving steaming to replace boiling gave higher moisture content but resulted in lower reducing sugar which was related with higher sensoric taste and colour scores. All the modified processes gave acceptable products. Modification II even resulted in better overall aceptability of the dodol compared to that of the traditional process, although the value for texture was less than that of the traditional dodol due to higher moisture content. Further, Modification H needed less time than the traditional method did.